PENGARUH IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. BANK DANAMON SIMPAN PINJAM UNIT METRO - Astuti, Hesti Widi; Tantowi, Ridwan (Jurnal Bisnis Darmajaya, 2017)
This study aims to determine the effect of organizational climate on employee performance at PT. Bank Danamon Savings and Loans Unit Metro, so it can be obtained the actual experience of the problems faced by PT. Bank Danamon Metro Unit and can be used as consideration to address the problems faced by PT. Bank Danamon Metro Unit. In this study, data analysis tool used is validity, reliability, simple linear regression, and t test. Methods of data collection was obtained from primary data sourced directly from employees working at PT. Bank Danamon Metro units totaling 35 people. From the results, a simple regression equation Y = 28,466 + 0,549X. Constant value (a) is 28,466 means if the value of variable X has not changed one unit, it will affect employee motivation of 28,466 units. Organizational culture variable coefficient value is 0,549, meaning that whenever there is a change of 1 unit, then it will affect the motivation of employees amounted to 0,549 units. From the results, the results of the t test of 8.128 indicates that the variable performance of employees affected by organizational climate variables.Keywords: Organizational Climate and Performance.